PANDANGAN FILSAFAT TERHADAP PELAKSANAAN PENDIDIKAN PADA MASA PANDEMI COVID-19 - Dewi Oktasari; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Journal of Innovation Research and Knowledge, 2022)
The work of philosophy is very important in interpreting every problem in life, including the problem of the pandemic of Covid-19. The keywords for interpreting and understanding the problem are humans and science. Advanced science is able to usher in humans at the peak of science. Meanwhile, education has a huge impact during the pandemic of Covid-19. Every aspect of learning is required with an online scheme from home. This requires the readiness of parents when guiding their children in carrying out learning, both knowledge and morals (attitudes). This study aims to explain philosophical views on the implementation of education for the pandemic of Covid-19. The study in this research is in the form of a literature review. In this study the data imposed from search results from electronic scientific journals obtained in the 2020-2022 period. The results of this study (1) Education during the pandemic experienced many obstacles, both from students, educators, and parents; (2) the application of education during a pandemic in a philosophical view involves basic human concepts (humanism), character education, and educational philosophy; (3) the philosophy of humanism is a fundamental study in the implementation of education for the pandemic of Covid-19; (4) during the pandemic of Covid-19, the philosophy of education with the flow of progressivism plays a role in providing direction for the implementation of flexible learning and can align with the evolution of science and technology.